Effectiveness of Maternal Transmission Risk Stratification in Identification of Infants for HIV Birth Testing: Lessons From Zimbabwe. (1st July 2020) - Mafaune, Haurovi W.; Sacks, Emma; Chadambuka, Addmore; Musarandega, Reuben; Tachiwenyika, Emmanuel; Simmonds, Francis M.; Nyamundaya, Tichaona; Cohn, Jennifer; Mahomva, Agnes; Mushavi, Angela
Abstract : Background: In 2017, Zimbabwe adopted a modified version of the World Health Organization 2016 recommendation on HIV birth testing by offering HIV testing at birth only to infants at "high risk" of HIV transmission. There is limited evidence on the effectiveness of this approach. Our study assessed the sensitivity and specificity of birth testing "high risk" infants only. Methods: We conducted a cross-sectional study at 10 health facilities from November 2018 to July 2019. A nucleic acid test for HIV was performed on all HIV-exposed infants identified within 48 hours of life, irrespective of risk status. Univariate and bivariate analyses were used to estimate the performance of the risk screening tool. Results: HIV nucleic acid test was successfully performed on 1970 infants (95%), of whom 266 (13.5%) were classified as high-risk infants. HIV prevalence for all infants tested was 1.5% (95% CI: 1% to 2%), whereas prevalence among high-risk infants and low-risk infants was 6.8% (95% CI: 3.7% to 9.8%) and 0.6% (95% CI: 0.3% to 1%) respectively. Sensitivity and specificity of the maternal risk screening tool was at 62.1% (95% CI: 44.4% to 79.7%) and 87.2% (95% CI: 85.7% to 88.7%), respectively; positive and negative predictive values were 6.8% (95% CI: 3.7% to 9.8%) and 99.4% (95% CI: 99.0% to 99.7%) respectively. Conclusions: Despite high negative predictive value, sensitivity was relatively low, with potential of missing 2 in every 5 HIV infected infants. Given the potential benefits of early ART initiation for all exposed infants, where feasible, universal testing for HIV-exposed infants at birth may be preferred to reduce missing infected infants.